Cadmium-Induced Cell Homeostasis Impairment is Suppressed by the Tor1 Deficiency in Fission Yeast - Požgajová, Miroslava; Navrátilová, Alica; Šebová, Eva; Kovár, Marek; Kačániová, Miroslava (International journal of molecular sciences, 2020)
Cadmium has no known physiological function in the body; however, its adverse effects are associated with cancer and many types of organ system damage. Although much has been shown about Cd toxicity, the underlying mechanisms of its responses to the organism remain unclear. In this study, the role of Tor1, a catalytic subunit of the target of rapamycin complex 2 (TORC2), in Cd-mediated effects on cell proliferation, the antioxidant system, morphology, and ionome balance was investigated in the eukaryotic model organism Schizosaccharomyces pombe. Surprisingly, spectrophotometric and biochemical analyses revealed that the growth rate conditions and antioxidant defense mechanisms are considerably better in cells lacking the Tor1 signaling. The malondialdehyde (MDA) content of Tor1-deficient cells upon Cd treatment represents approximately half of the wild-type content. The microscopic determination of the cell morphological parameters indicates the role for Tor1 in cell shape maintenance. The ion content, determined by inductively coupled plasma optical emission spectroscopy (ICP-OES), showed that the Cd uptake potency was markedly lower in Tor1-depleted compared to wild-type cells. Conclusively, we show that the cadmium-mediated cell impairments in the fission yeast significantly depend on the Tor1 signaling. Additionally, the data presented here suggest the yet-undefined role of Tor1 in the transport of ions.
Keywords: homeostáza; vztah mezi dávkou a účinkem léčiva; oxidační stres; kadmium; Cadmium; Oxidative Stress; proteinkinasy; Homeostasis; Dose-Response Relationship, Drug; Schizosaccharomyces pombe - proteiny; Malondialdehyde; Gene Expression Regulation, Fungal; Schizosaccharomyces; ionty; regulace genové exprese u hub; Protein Kinases; malondialdehyd; Ions; Schizosaccharomyces pombe Proteins